Analysis and Evaluation of Structural Life Cycle for Urban Rail Transit Vehicle - XIAO Yan-jun (机车电传动)
Based on the structured life cycle theory analysis of urban rail transit vehicle systems application, five key stages in whole life cycle of urban rail transit vehicle systems were put forward, including vehicle selection of overall planning stage, two main interfaces of design stage, process control and testing of manufacturing stage, various systems interface matching of commissioning stage and final actual verification of operation maintenance stage, which were helpful to implement vehicle system whole life cycle effective control from urban rail transit planning to last operation.